THE WAYS OF IMPROVING LISTENING SKILLS OF A1 LEVEL LEARNERS - Jabborova Shoira; Eshboyeva Madina (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The main purpose of this study was to investigate the effect of listening comprehension of A1 learners. We often think of speaking and writing as the most challenging of the four language skills but what about the receptive skills? With reading, learners have time to think, but listening in another language presents a very different set of challenges for the learner. How often have we heard learners complain “it’s too fast” Teaching English listening skills to A1 learners is a foundational and crucial aspect of their language acquisition journey. It is essential to tailor listening activities to their beginner level, focusing on simple vocabulary, basic grammar structures, and familiar contexts. By incorporating engaging and interactive listening exercises, educators can effectively support A1 learners in developing their auditory comprehension and spoken language abilities.